PENGARUH FINANCIAL DISTRESS, GENDER KOMITE AUDIT DAN UKURAN KAP TERHADAP AUDIT REPORT LAG DENGAN AUDIT TENURE SEBAGAI VARIABEL MODERASI - Wigia Pritami; Tomi Riyadi (Jurnal Nusa Akuntansi, 2026)
Companies listed on the Indonesia Stock Exchange (IDX) are required to publish audited financial reports. However, companies face both internal and external challenges in the process. This study aims to examine the effect of financial distress, audit committee gender, and public accounting firm size on audit report lag, with audit tenure as a moderating variable. The population of this study consists of property and real estate companies listed on the Indonesia Stock Exchange during 2020–2024. The results of the t-test show that financial distress and audit committee gender have an effect on audit report lag, while public accounting firm size does not. The results of the moderation test indicate that audit tenure is able to moderate the relationship between audit committee gender and audit report lag. However, audit tenure is not able to moderate the relationship between financial distress and public accounting firm size with audit report lag.